Deep desulfurization of fuels: Are deep eutectic solvents the alternative for ionic liquids?. (1st June 2021) - Lima, Filipa; Branco, Luis C.; Silvestre, Armando J.D.; Marrucho, Isabel M.
Highlights: DES are viable alternatives to Ionic Liquids in Desulfurization Processes. DES present environmental and economic advantages in Desulfurization. DES stability, recycling and disposal are crucial to Desulfurization market. Urgent need to test the most promising DES in real matrices. Abstract: The impact of fossil fuels impurities on outdoor air pollution is today a matter of great concern, with the transportation sector playing a major role. Given global efforts to reduce sulfur oxides emissions, and the increasingly tighter legislations, removal of sulfur contaminants liquid highway fuels is a pressing issue worldwide. The purpose of this review is to provide a detailed state of the art review concerning the use of deep eutectic solvents (DES) in the removal of sulfur pollutants from transportation fuels. Furthermore, a comparative evaluation regarding the use of these solvents versus Ionic Liquids (ILs) is also provided, taking into account several aspects, such as, evolution of technologies, solvents composition, extraction efficiencies and environmental and economic considerations. The large gap in terms of efficiency of the reported technologies, either using ILs or DES, between simulated matrices and real fuels is also discussed, highlighting the importance of academia and industry hand in hand work.